2014
DOI: 10.1002/app.40901
|View full text |Cite
|
Sign up to set email alerts
|

Polymer‐based route to ferroelectric lead strontium titanate thin films

Abstract: Ceramic films with high values of ferroelectricity, piezoelectricity, and dielectricity with perovskite structure, like lead zirconate titanate (PZT, PbZrxTi1‐xO3), lead strontium titanate (PST, PbxSr1‐xTiO3), and barium strontium titanate (BST, BaxSr1−xTiO3), are subjects of intensive research due to their use in sensors, energy harvesters, capacitors, and FeRAMs. Here a novel, simple way to produce micropatterned perovskite PST thin films on silicon substrates by a polymer‐based direct UV‐lithography process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The PST films were manufactured using a polymer-based deposition and patterning direct UV-lithographic process. We reported this process in detail in a publication (Benkler et al 2014). Due to the simple sol synthesis and the straightforward process, this method is an interesting alternative to other deposition and patterning processes.…”
Section: Sensor Design and Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…The PST films were manufactured using a polymer-based deposition and patterning direct UV-lithographic process. We reported this process in detail in a publication (Benkler et al 2014). Due to the simple sol synthesis and the straightforward process, this method is an interesting alternative to other deposition and patterning processes.…”
Section: Sensor Design and Technologymentioning
confidence: 99%
“…It was shown that 4H-SiC 80 µm thick diaphragms can be fabricated five times faster with laser ablation in comparison to (RIE) (Vanko et al 2013). We now also investigate ferroelectric thin films as they can be deposited and micro-patterned by a direct UVlithography method after the ablation process for a specific membrane design (Benkler et al 2014). The risk to harm or damage the function of thin films can be eliminated by that fabrication procedure.…”
Section: Introductionmentioning
confidence: 99%